Acute cannabidiol administration reduces alcohol craving and cue-induced nucleus accumbens activation in individuals with alcohol use disorder: the double-blind randomized controlled ICONIC trial - Vetter, Sina; Teetzmann, Anton; Baeßler, Joscha; Schreckenberger, Lena; Zaiser, Judith; Pfisterer, Marlen; Stenger, Manuel; Bach, Patrick (Molecular psychiatry, 2024)
Although alcohol use disorder (AUD) is highly prevalent, only a few medications are approved for its treatment leaving much room for improvement. Cannabidiol (CBD) might be a particularly promising candidate, with preclinical data suggesting that CBD is effective in targeting AUD symptoms and disease processes that drive alcohol use and relapse, due to its anti-craving, stress-reducing, and anti-compulsive effects. Here we report data from the double-blind randomized controlled ICONIC trial that compared the effects of a single dose of 800 mg cannabidiol against placebo (PLC) in N = 28 individuals with AUD. Cue-induced nucleus accumbens (NAc) activation, alcohol craving during a combined stress- and alcohol cue exposure session, as well as craving during an fMRI alcohol cue-reactivity task and CBD plasma levels served as outcomes. Individuals receiving CBD showed lower bilateral cue-induced NAc activation (tleft_NAc(23) = 4.906, p < 0.001, d = 1.15; tright_NAc (23) = 4.873, p < 0.001, d = 1.13) and reported significantly lower alcohol craving after a combined stress- and alcohol cue exposure session (Fgroup(1,26) = 4.516, p = 0.043, eta2 = 0.15) and during the fMRI cue-reactivity task (Fgroup(1,24) = 6.665, p = 0.015, eta2 = 0.23). CBD levels were significantly higher in the CBD group (t(25) = 3.808, p < 0.001, d = 1.47) and showed a significant negative association with alcohol craving during the cue exposure experiment (r = −0.394, pFDR = 0.030) and during fMRI (r = −0.389, pFDR = 0.030), and with left and right NAc activation (rleft_NAc = −0.459, pFDR = 0.030; rright_NAc = −0.405, pFDR = 0.030). CBD’s capacity to reduce stress- and cue-induced alcohol craving and to normalize NAc activation - a region critical to the pathophysiology of AUD - contribute to understanding the neurobiological basis of its clinical effects and support its potential as a treatment option for AUD. Clinical Trials Registry: DRKS00029993.
Online veröffentlicht: 12. Dezember 2024
Gesehen am 12.03.2025